2016
DOI: 10.1111/joop.12152
|View full text |Cite
|
Sign up to set email alerts
|

Linking educational diversity and team performance: Team communication quality and innovation team climate matter

Abstract: Linking educational diversity and team performance: Team communication quality and innovation team climate matter V ıctor Valls*, Vicente Gonz alez-Rom a and In es Tom as Idocal, University of Valencia, Spain This study examines the influence of education level diversity on team communication quality and team performance. Specifically, we propose a moderated mediation model with team communication quality as a mediator in the relationship between education level diversity and team performance, and with inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…Secondly, the causal direction of relationships between psychological capital, burnout and PWB remains unclear, given the use of a time lagged design. Adopting a time-lagged design we overcome many limitations associated with cross-sectional research and it let us to test the hypothesized relationship in a more rigorous manner (Valls et al, 2016 ). To make the direction of relationships between these variables clearer, longitudinal studies would be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the causal direction of relationships between psychological capital, burnout and PWB remains unclear, given the use of a time lagged design. Adopting a time-lagged design we overcome many limitations associated with cross-sectional research and it let us to test the hypothesized relationship in a more rigorous manner (Valls et al, 2016 ). To make the direction of relationships between these variables clearer, longitudinal studies would be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…For example, by utilizing the interactionist model of creativity (Woodman & Schoenfeldt, 1990) and the input-process-output model for team effectiveness (McGrath, 1984), Somech and Drach-Zahavy (2013) found that team creativity only enhanced innovation implementation when team innovation climate was high. Valls, Gonzalez-Roma, and Tomas (2016) established that when team innovation climate was higher, the influence of team educational diversity on team communication quality was stronger and the influence of team educational diversity on team performance through team communication quality was also higher. Charbonnier-Voirin, El Akremi, and Vandenberghe (2010) established that the influence of transformational leadership on employees' adaptive performance was stronger when team innovation climate was higher.…”
Section: Innovation Climate As a Moderatormentioning
confidence: 99%
“…Chen and Hou (2016), based on social learning theory (Bandura, 1997), found that the indirect effect of ethical leadership on individual creativity via voice behaviour was stronger when team innovation climate was higher. Valls, Gonzalez-Roma, and Tomas (2016) established that when team innovation climate was higher, the influence of team educational diversity on team communication quality was stronger and the influence of team educational diversity on team performance through team communication quality was also higher. Underpinning this study was the categorization-elaboration model (CEM; van Knippenberg, De Dreu, & Homan, 2004), which posits that the information/decision-making perspective and social categorization perspective can jointly be used to predict effects of diversity.…”
Section: Innovation Climate As a Moderatormentioning
confidence: 99%
“…Knippenberg, Dawson, West, & Homan, 2011). Additionally, groups obtain a greater task understanding by reflecting upon and modifying their functioning (i.e., team reflexivity; Schippers, Den Hartog, Koopman, & Wienk, 2003;Van Ginkel, Tindale, & Van Knippenberg, 2009), and by building an open and trusting climate for debate and conflict (e.g., Mitchell, Nicholas, & Boyle, 2009;Olson, Parayitam, & Bao, 2007;Simons, Pelled, & Smith, 1999;Valls, González-Romá, & Tomás, 2016).…”
Section: Promoting Diversity's Potentialmentioning
confidence: 99%
“…This shared task understanding can be facilitated by stimulating a collective understanding of who knows what within the group (i.e., transactive memory system; Heavey & Simsek, ) or by stressing shared group goals (e.g., Van Knippenberg, Dawson, West, & Homan, ). Additionally, groups obtain a greater task understanding by reflecting upon and modifying their functioning (i.e., team reflexivity; Schippers, Den Hartog, Koopman, & Wienk, ; Van Ginkel, Tindale, & Van Knippenberg, ), and by building an open and trusting climate for debate and conflict (e.g., Mitchell, Nicholas, & Boyle, ; Olson, Parayitam, & Bao, ; Simons, Pelled, & Smith, ; Valls, González‐Romá, & Tomás, ).…”
Section: Diversity: Managing Its Problems and Potentialmentioning
confidence: 99%